2001
DOI: 10.1592/phco.21.7.731.34570
|View full text |Cite
|
Sign up to set email alerts
|

Practice‐Based Research: Lessons from Community Pharmacist Participants

Abstract: We designed this project to determine community pharmacists' opinions regarding the challenges and motivations of their recent participation in a pharmacy practice-based research study At the conclusion of a randomized, multicenter study, 87 community pharmacist-investigators were sent a questionnaire that explored four areas: motivating factors to participate, barriers to participation, communication tools used by study coordinators, and design issues for future studies. Fifty-eight (67%) completed questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 31 publications
9
64
2
2
Order By: Relevance
“…Simpson et al reported that time was the greatest barrier to participation of pharmacy practice-based research in Canada [6]. In a systematic review of 15 studies completed in the UK, Australia, and Canada, the barriers were: lack of time and workload; insufficient or lack of funds; and lack of research knowledge, training, mentorship, and support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpson et al reported that time was the greatest barrier to participation of pharmacy practice-based research in Canada [6]. In a systematic review of 15 studies completed in the UK, Australia, and Canada, the barriers were: lack of time and workload; insufficient or lack of funds; and lack of research knowledge, training, mentorship, and support.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that there are some barriers for pharmacists to engage in practice research [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the study limitations is the opportunistic recruitment of patients in the community pharmacy affecting the generalisability of the sample. This has been reported as a limitation in other studies of the same design [33]. It may be attributed to pharmacists' inexperience and initial hesitation with informed consent and enrollment procedures.…”
Section: Discussionmentioning
confidence: 95%
“…It may be attributed to pharmacists' inexperience and initial hesitation with informed consent and enrollment procedures. Simpson et al (2001) reported that patients were sometimes surprised when approached by their pharmacist for participation in a ''research study'' [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies during this period indicated increased awareness and positive attitude towards research among pharmacists, mostly in the community setting (Rosenbloom et al 2000;Simpson et al 2001;Saini et al 2006;Armour et al 2007;Peterson et al 2009). Future development of community pharmacy practice and new practice models could be among the motivational factors for this trend.…”
Section: -2009mentioning
confidence: 99%